Revolutionizing Nursing Higher Education: Virtual Reality-Based Elderly Care Service Practice Simulation: A Systematic Review - Asmirajanti, Mira; Antia, Antia; Tamly, Wahyu (JURNAL INFO KESEHATAN, 2024)
Nursing services in the elderly population play an important role in modern nursing practice, especially with the growth in the number of elderly. The presence of competent and trained nurses is crucial to providing effective care to this demographic. One potential method to improve nursing students' understanding and skills in aged care is the utilization of Virtual Reality (VR) technology to simulate aged services.  This study aims to identify the virtual reality-based elderly nursing service simulation revolution through a systematic review. Systematic Literature Review is conducted by searching the data sources ScienceDirect, Pubmed, CINAHL, and Google Scholar. Inclusion and exclusion criteria based on the PICO approach, are used to select suitable articles, with a range of publication years from 2018 to 2022. Of the 2241 articles identified at the start of the study, 46 relevant articles were selected after narrowing through a review of titles and abstracts. Of these, 24 articles were selected for further analysis according to the research theme. The results showed that the use of VR technology significantly increased the competence of nursing students, and increased clinical skills, confidence, and understanding of human physiological anatomy.  VR simulations have proven effective in providing services to elderly patients, including teaching elderly oral hygiene, training in the prevention of dizziness and falls, practicing ADL, and teaching relaxation techniques to reduce pain and symptoms of depression. The new opportunities in nursing higher education innovation, VR technology provides an immersive experience for students in caring for an aging population that is growing, along with technological developments.